2020
DOI: 10.1002/wer.1384
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure to anionic surfactants (SDBS and SDS) on nitrogen removal of aerobic denitrifier

Abstract: In order to explain the effect of anionic surfactants on aerobic denitrification in the urban river, sodium dodecyl benzene sulfonate (SDBS) and sodium dodecyl sulfonate (SDS) were added in aerobic denitrifier and the efficiency of nitrogen removal, microbial mechanisms, and enzyme activity was investigated in this study. The results showed that the total nitrogen (TN) and the nitrate nitrogen (NO − 3 − N) removal efficiency decreased as an increase of SDBS concentration. In contrast, 59.70% of the TN and 75.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…On Day 21, at a dosage of 10 mg/L SMX, a rise in nitrate removal led slight accumulation of nitrite. The accumulation of nitrite during aerobic denitrification was due to inhibition of aerobic denitrifiers by antibiotic toxicity (Yin et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…On Day 21, at a dosage of 10 mg/L SMX, a rise in nitrate removal led slight accumulation of nitrite. The accumulation of nitrite during aerobic denitrification was due to inhibition of aerobic denitrifiers by antibiotic toxicity (Yin et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…2, was expected due to the perceived negative effects of surfactants on sewer biofilm activity. The presence of SDBS in high concentrations has been reported to result in a decrease in microbial activity through the direct interaction between SDBS and microorganisms [17]. Brandt et al [18] reported that microbial inhibition by surfactants occurred through the interaction of SDBS with the lipid cell membrane, causing permeability changes in the microbial cell.…”
Section: Effect Of Anionic Surfactant On Ocrmentioning
confidence: 99%
“…In the field of wastewater treatment, Li et al [14] found in 2020 that SDBS can affect the biological nitrogen and phosphorus removal efficiency in high-salinity wastewater treatment. YIN C et al [15] also found that surfactants can have a serious impact on denitrification-related bacteria in wastewater treatment in the same year. In the field of coal dust, J Meng et al [16] found in 2021 that surfactants can also affect the dispersion of coal dust.…”
Section: Introductionmentioning
confidence: 96%